Extremes floods of Venice: characteristics, dynamics, past and future evolution - Lionello, Piero; Barriopedro, David; Ferrarin, Christian; Nicholls, Robert J.; Orlic, Mirko; Raicich, Fabio; Reale, Marco; Umgiesser, Georg; Vousdoukas, Michalis; Zanchettin, Davide (2020)
Floods in the Venice city centre result from the superposition of several factors: astronomical tides, seiches and atmospherically forced fluctuations, which include storm surges, meteotsunamis, and surges caused by planetary waves. All these factors can contribute to positive sea-level anomalies individually and can also result in extreme sea-level events when they act constructively. The largest extreme sea level events have been mostly caused by storm surges produced by the Sirocco winds. This leads to a characteristic seasonal cycle, with the largest and most frequent events occurring from November to March. Storm surges can be produced by cyclones whose centers are located either north or south of the Alps. The most intense historical events have been produced by cyclogenesis in the western Mediterranean, to the west of the main cyclogenetic area of the Mediterranean region in the Gulf of Genoa. Only a small fraction of the interannual variability of extreme sea levels is described by fluctuations in the dominant patterns of atmospheric circulation variability over the Euro-Atlantic sector. Therefore, decadal fluctuations of sea-level extremes remain largely unexplained. In particular, the effect of the 11-year solar cycle appears to be small, non-stationary or masked by other factors. The historic increase in the frequency of extreme sea levels since the mid 19 th Century is explained by relative sea level rise, with no long term trend in the intensity of the atmospheric forcing. Analogously, future regional relative mean sea level rise will be the most important driver of increasing duration and intensity of Venice floods through this century, overwhelming the small decrease in marine storminess projected during the 21 century. Consequently, the future increase of extreme sea levels covers a large range, partly reflecting the highly uncertain mass contributions to future mean sea level rise from the melting of Antarctica and Greenland ice-sheets, especially towards the end of the century. In conclusion, for a high emission scenario the magnitude of 1-in-100 year sea level events at the North Adriatic coast is projected to increase up to 65 % and 160 % in 2050 and 2100, respectively, with respect to the present value, and subject to continued increase thereafter. Local subsidence can further contribute to the future increase of extreme sea levels. This analysis shows the need for adaptive planning of coastal defenses with solutions that can be adopted to face the large range of plausible future sea-level extremes.